STUDI KOMPARASI KINERJA GEDUNG BERTINGKAT SISTEM GANDA RANGKA PEMIKUL MOMEN KHUSUS DAN MENENGAH DI KOTA MANADO - Abdul Ahad Ghifar Ente; Marthin Dody Josias Sumajouw; Steenie Edward Wallah (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
Seismic designs for high-rise buildings in the city of Manado, are generally designed using a special reinforced concrete moment frames, but looking at the requirements of SNI 1726-2019 in the city of Manado with seismic design category D, multi-storey building plans can be designed using a dual systems with intermediate moment frames by paying attention to the building height limit of 48 meters. This study will compare the planning efficiency of a dual systems with intermediate moment frames to that of a dual systems with special moment frames in terms of dimensions, details of reinforcement and structural performance with a building height not exceeding 48 meters. The building simulation has a building length and width of 35 x 25 meters, then the height between floors is 4 meters with a building height of 16 meters (Low Rise Building/LRB), 32 meters (Middle Rise Building/MRB) and 48 meters (High Rise Building/HRB). The ratio of the longitudinal reinforcement area of the beam elements in the double system of intermediate moment frames is not more efficient than the double system of special moment bearing frames with the respective efficiency levels in the HRB, MRB and LRB models being -13.33%, -12.95% and -5.00%. Comparison of area of transverse reinforcement of column elements Double Intermediate Moment Resisting Frames are more efficient than Special Moment Bearing Double Systems with their respective efficiency levels in the HRB model. MRB and LRB is 18.35%. 19.47% and 34.68%. Comparison of structural performance in the Dual Intermediate Moment Resisting Frame system is more efficient than the Special Moment Resisting Double Frame System with an efficient rate of 22.85% for each model HRB, MRB and LRB. 20.95% and 12.63% in the X direction and 25.43%. 21.89% and 17.97% in the Y direction.